Bawaslu's Strategy in Increasing Community Participation: Preventive Efforts in Supervision and Prevention of Violations in the 2024 Regional Election in Surabaya - Faizal Rusdi Bachtiar; Amelia Kartika Oktaviani; Muhammad Hanif Baihaqi; Hasan Ismail (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2024)
This study aims to analyze the strategy of the Surabaya City Election Supervisory Agency (Bawaslu) in increasing public participation as a preventive effort in supervising the 2024 Pilkada. Bawaslu uses a collaborative governance approach that involves non-government actors in decision-making and utilizes digital technology through the Sigaplapor platform to facilitate reporting of election violations. The use of social media and training for volunteer supervisors are also part of this strategy. The results of the study show that public participation through a collaborative approach and digital technology has succeeded in strengthening election supervision. However, there are still challenges in the form of limited digital literacy and resistance from certain political actors. This policy requires increasing digital literacy, strengthening cooperation with law enforcement, and increasing digital security to ensure the sustainability of inclusive, transparent, and accountable election supervision.